Impact of mesoporous silica on the chemical degradation of Praziquantel upon grinding - Šagud, Ivana; Zanolla, Debora; Zingone, Guglielmo; Perissutti, Beatrice; Škorić, Irena (Comptes Rendus. Chimie, 2021)
Praziquantel and Syloid 244 FP (amorphous silicon dioxide) were ground in a vibrational mill in standard conditions ($15^{′}$ or $30^{′}$ at 25 Hz). Amorphous solid dispersions were obtained in a very short grinding time (15 min), as testified by DSC, PXRD and ESEM analyses. Samples ground at $15^{′}$ and $30^{′}$ showed the presence of the same degradation product, as was evident from UPLC, MS and NMR analyses. This short paper brings to light the tremendous lattice de-structuration ability of Syloid 244 FP upon grinding toward Praziquantel as well as its detrimental influence on promoting chemical degradation through ring opening and oxidation.